Nanocomposite polymer electrolytes of sodium alginate and montmorillonite clay - Sentanin, Franciani C. (2021)
Nanocomposite polymer electrolytes (NPEs) were synthesized using sodium alginate (Alg) and either sodium (SCa-3-Na+)- or lithium (SCa-3-Li+)-modified montmorillonite clays. The samples were characterized by structural, optical, and electrical properties. SCa-3-Na+ and SCa-3-Li+ clays’ X-ray structural analyses revealed peaks at 2θ = 7.2° and 6.7° that corresponded to the interlamellar distances of 12.3 and 12.8 Å, respectively. Alg-based NPEs X-ray diffractograms showed exfoliated structures for samples with low clay percentages. The increase of clay content promoted the formation of intercalated structures. Electrochemical Impedance Spectroscopy revealed that Alg-based NPEs with 5 wt% of SCa-3-Na+ clay presented the highest conductivity of 1.96 × 10−2 S/cm2, and Alg with 10 wt% of SCa-3-Li+ showed conductivity of 1.30 × 10−2 S/cm2, both measured at 70 °C. From UV-Vis spectroscopy, it was possible to infer that increasing concentration of clay promoted a decrease of the samples’ transmittance and, consequently, an increase of their reflectance.